1993
DOI: 10.1111/j.1095-8649.1993.tb01155.x
|View full text |Cite
|
Sign up to set email alerts
|

Community ecology of the parasites of adult spot, Leiostomus xanthurus, and Atlantic croaker, Micropogonias undulatus (Sciaenidae) in the Cape Hatteras region

Abstract: Twenty‐three species of metazoan parasites were recorded from adult spot and 26 from adult croaker. Of the 33 parasitic species found, 17 occurred in both spot and croaker. No significant differences in intensity of parasites occurred between sexes of either spot or croaker. All of the parasites had over‐dispersed, or clumped, distributions among hosts. Adult spot and croaker collected offshore had much greater species‐richness, diversity, and total number of individual parasites than juvenile fishes collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
1
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 15 publications
4
7
1
1
Order By: Relevance
“…Parasitic h (Nahhas & 2009) In general, trematodes and nematodes are the most numerous parasities species in marine fish, among them the sciaenids (Rohde & Heap, 1998;Zander et al, 1999), including those from tropical (Moravec et al, 1997;Sabas & Luque, 2003;Luque & Poulin, 2007), and temperate latitudes (Zander et al, 1999;Madhavi & Sai-Ram, 2000), and Our results also showed this condition, these results are similar to records in other sciaenids from the USA (Thoney, 1991(Thoney, , 1993, Peru (Oliva & Luque, 1998), and Brazil (Chaves & Luque, 1999;Alves & Luque, 2001;Sabas & Luque, 2003), adding that in our records of the parasites of U. coroides, the number of acanthocephalans (4 sp.) is high with respect to the registry for other scianids.…”
Section: Discusssupporting
confidence: 87%
See 1 more Smart Citation
“…Parasitic h (Nahhas & 2009) In general, trematodes and nematodes are the most numerous parasities species in marine fish, among them the sciaenids (Rohde & Heap, 1998;Zander et al, 1999), including those from tropical (Moravec et al, 1997;Sabas & Luque, 2003;Luque & Poulin, 2007), and temperate latitudes (Zander et al, 1999;Madhavi & Sai-Ram, 2000), and Our results also showed this condition, these results are similar to records in other sciaenids from the USA (Thoney, 1991(Thoney, , 1993, Peru (Oliva & Luque, 1998), and Brazil (Chaves & Luque, 1999;Alves & Luque, 2001;Sabas & Luque, 2003), adding that in our records of the parasites of U. coroides, the number of acanthocephalans (4 sp.) is high with respect to the registry for other scianids.…”
Section: Discusssupporting
confidence: 87%
“…On the other hand, the parasite communities in five sciaenids are as rich and diverse as those in marine hosts in temperate (Châari et al, 2015) and tropical zones (Luque & Poulin, 2007;Madhavi & Triveni-Lakshmi, 2012), both in community components and infracommunities, especially with parasitic helminth communities of sciaenids from the west coast of the Atlantic. e.g., Leiostomus xanturus (S = 19, S = 6±1.9, H' = 1.4±0.69) and Micropogonias undulatus (S = 21, S = 7.3±2.3, H'= 1.8±0.63) (Thoney, 1993); Cynoscion guatucupa (S = 15, S = 4.6±1.8) and Macrodon ancylodon (S = 14, S = 2.8±1.3) (Sabas & Luque, 2003); Menticirrhus americanus (S = 12, S = 2.2±1.3, H = 0.56±0.28) (Chaves & Luque, 1999); Micropogonias furnieri (S = 20, S = 2.9±2, H = 0.49±0.41) (Alves & Luque, 2001), and Paralonchurus brasiliensis (S = 12, S = 2.1±0.9) . Finally, it has to be said that parasitic relations of hosts in wild populations, with biological, commercial and food relevance, and high farming potential, as those of sciaenids (Ohs et al, 2013), pose no zoonotic risk, and their parasitic helminth communities are rich and diverse.…”
Section: Discussmentioning
confidence: 99%
“…Las infracomunidades de helmintos de S. plagiusa fueron similares en el número promedio de especies (2 ± 0.55 -3 ± 0.66) (Cuadro 3) con otras especies de peces como Labrus merula (riqueza: 4.17 ± 0.90), Symphodus tinca (4.15 ± 1.29) (Campos y Carbonell, 1994) o Leiostomus xanthurus (6.0 ± 1.9) (Thoney, 1993). Los valores también son similares a los de otros peces tropicales pelágicos, como Trachinotus carolinus (4 ± 1 -6 ± 2) (Sánchez-Ramírez y , Menticirrhus ophicephalus (4.1 ± 1.5) (Luque y Oliva, 1999), y Epinephelus morio (4.11 ± 2.08) (Vidal-Martínez et al, 1998).…”
Section: Hospederounclassified
“…(Par), Graffilid (Gra). Dotted horizontal lines represent the limits of the study performed by Thoney (1993). Solid vertical lines represent the latitudinal range of each individual species.…”
Section: Resultsmentioning
confidence: 99%
“…Solid vertical lines represent the latitudinal range of each individual species. Asterisks denote those species not documented by Thoney (1993). …”
Section: Resultsmentioning
confidence: 99%